Pengaruh Pembayaran Digital terhadap Keberlangsungan Usaha pada UMKM Nyambowl - Ivtachul Ma'rifah; Yuli Supriyanto; Nugroho Wibowo; Arifina Rosi Damawati; Siti Umaira Nauvalia; Irvan Apriansyah (Fakultas Ekonomi Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2022)
The Covid-19 pandemic in Indonesia occurred in early 2020. This situation caused several economic activities to experience many changes, especially in terms of payment transactions. People prefer to transact online. Shopeepay, Qris, and transfers are the most widely used electronic payments by Indonesian people, especially college students. Therefore, this study aims to analyze digital payments on business continuity at Nyambowl SMEs. This study uses primary data obtained through direct observation and secondary data obtained by literture study . The research method that the writer uses is descriptive method. The results of the analysis show that the digital payment method is felt to be more efficient and has an impact on business continuity at Nyambowl MSME as evidenced by the increase in profit earned from transactions with digital payments. Keywords: Digital payments, SMEs, efficient.